Dampak Penetapan Izin Praktek Tambang Emas Tumpang Pitu Perspektif Fikih Sosial KH. Sahal Mahfudh: The Impact of the Tumpang Pitu Gold Mining Permit from KH. Sahal Mahfudh’s Social Fiqh Perspective - Zainul Mun'im (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Due to its significant impact on the environment, gold mining is often a particular concern. This paper examines the effect of granting gold mining permits on Mount Tumpak Pitu, Banyuwangi Regency, East Java, from the perspective of social fiqh developed by Sahal Mahfudh. Social fiqh prioritizes benefits framed in maqâshid al-syarî'ah, with indicators of hifz al-dîn (existence of religion), al-nafs (salvation of the soul), al-'aql (health of the mind), al-mâl (safety of property), al-nasl (safety of honor) and al-bî'ah (environmental sustainability). This research used the normative juridical approach and qualitatively analyzed data collected through literature and field studies. The research results show that granting gold mining permits was not accompanied by adequate supervision from the authority. This gives rise to mining practices that are not environmentally friendly and do not fulfill the basic principles of environmental ethics in Sahal Mahfudh’s social fiqh.